Lived experiences of female patients aged 15-49 years undergoing treatment for multi-drug resistant tuberculosis (MDR-TB) in Lira Regional Referral Hospital, Uganda - Kizito Omona; Christopher Ogwang (Taylor & Francis Group, 2024)
Abstract: Multidrug-resistant tuberculosis (MDR-TB) is a major public health hazard on a global scale. It is a kind of tuberculosis (TB) infection produced by bacteria resistant to at least two of the most effective first-line anti-tuberculosis (anti-TB) drugs: isoniazid and rifampicin. In numerous health care facilities around Uganda, MDR-TB patients have bad experiences. The purpose of this study was to investigate the lived experiences of female patients aged 15 to 49 years receiving treatment for MDR-TB at Lira Regional Referral Hospital, Uganda. Using a method of purposive sampling, a phenomenological qualitative study was done among female patients aged 15 to 49 receiving treatment for multidrug-resistant tuberculosis at Lira Regional Hospital. Data was collected using an English-translated Lango guide for in-depth interviews. Data was entered manually and analyzed using version 13 of the qualitative program NVIVO. It was discovered that the spouses of female MDR-TB patients lacked social support. Female patients with a history of tuberculosis prior to MDR-TB had stronger family support systems. MDR-TB diagnosis was strongly related with shock, anxiety, and denial. The majority of patients indicated that proper information on probable side effects allowed them to successfully complete MDR-TB treatment. Compared to other health centres in the district, the MDR-TB services at Lira Regional Referral were easily accessible and staffed by friendly medical personnel. In conclusion, female patients receiving MDR-TB treatment represent a unique population, and family support and care had a significant impact on the success of MDR-TB treatment among them.